The calculation of low voltage solution based on state space search method in ill-conditioned system - Shahriari, A.; Mokhlis, Hazlie; Bakar, A.H.A.; Karimi, M.; Laghari, J.A.; Kazeminezad, M. (2012)
This paper implements the State Space Search Method (SSSM) in polar coordinate form to calculate low voltage solution and Maximum Loading Point of system in ill conditioned system. SSSM modifies the direction of state variable (buses voltage and phase) by using optimal multiplier in order to converge load flow equations in ill conditioned system. The privilege of SSSM emerges in the keeping dimension of load flow jacobian matrix constant. While another method such as continuation and homotopy methods change the framework of jacobian matrix based on predictor and corrector in term of increasing load demand. Indeed, the calculation process of SSSM is based on standard Newton Raphson load flow method. The validation of SSSM is shown by the testing IEEE test systems of 14 and 30 in well and maximum loading point as ill-conditioned systems.